Difficulties Experienced by School Principals in the Interior and Exterior Engineering Spaces of the School Building - كيخيا, محمد; سعيد, نسيبة; شعبان, نغم (Latakia University Journal -Engineering Sciences Series, 2022)
The engineering spaces are an important part of the architectural product, especially in the educational construction. The physical characteristics, the functional methodology and the form are the container in which the students interact with the school building and based on the design and activation of the educational process.The present study deals with the difficulties faced by principals of secondary schools in the interior and exterior engineering spaces of the school building in Lattakia, from the point of view of a sample of secondary school principals in Lattakia city. In order to achieve the objectives of the research a questionnaire was designed to influence the behavioral and psychological systems of the managers in the external architectural spaces of the building School, and problems related to the interior architectural spaces of the school building. After study and analysis, the research results in the following results;-1- The principals of secondary schools in Lattakia suffer from difficulties and problems they suffer in the interior and exterior engineering spaces of the school building in the longitudinal direction of separating the students in obtaining a sufficient quantity of light, in the design of the private halls and the drawing rooms and towards it and the sunlight emanating from the windows. The light in the classrooms is not distributed properly enough to perform the educational process and there is difficulty in the design site of the school and the lack of fit with neighboring buildings and with the effects of the climate of the coastal environment, and the constant tension of the principals of the school building by virtue of the main street, The students have to keep the distance they travel, which is more than 3 kilometers.-2- There are differences of statistical significance between the views of the sample members on the difficulties experienced by principals in the internal and external engineering spaces of the school building depending on the variable (gender, qualification.